Students’ Challenges and Self-Efficacy in Academic Writing and Research in ELT: A Descriptive Survey - Ulfiyati, Sofwa Maharina; Farida, Alief Noor (Universitas Nurul Jadid, 2025)
Academic writing and research proficiency are important for undergraduates in English Language Teaching (ELT), as they reflect the ability to express academic arguments and conduct evidence-based inquiry. Though indispensable, a great number of students still face problems while trying to master these skills, especially with the linguistic accuracy that is necessary, argument structure, anxiety related to writing, and proper use of research methodologies. There have been studies that focused on the difficulties experienced in writing, researches on skills, or self-efficacy separately, but only a few have analyzed the intersection of these areas in the ELT setting thus far. This research scrutinizes the hurdles that students encounter in academic writing and research along with their self-efficacy regarding such tasks. A quantitative descriptive survey design was adopted with a sample consisting of forty English Education students from Universitas Negeri Semarang who had already taken the courses Academic Writing and Research in ELT. A structured 51-item questionnaire was used to gather data, which was meant to assess students' difficulties in academic writing and research, The students' self-efficacy in these tasks was also evaluated. The data were analyzed using descriptive statistics and thematic analysis. The results of the analysis showed that the students performed at a moderate level of difficulty in writing (M = 3.17) and research (M = 3.20) with the greatest difficulty being about time management, writing anxiety, and data handling. Yet, the participants showed moderate to high self-efficacy in writing (M = 3.79) and research (M = 3.81), indicating strong confidence in conceptual understanding but limited assurance in analytical tasks. These findings suggest that, although students are sufficiently motivated and confident, they require further instructional assistance in research methodology, analytical processes, and academic writing conventions. The study suggests that including systematic instruction, scaffolded practice and formative feedback into ELT curricula can enhance both students’ technical competence and academic confidence, eventually developing independent reflective, and research-oriented English language educators.